High expression of EphA1 in esophageal squamous cell carcinoma is associated with lymph node metastasis and advanced disease. Issue 1 (12th July 2012) - Wang, Jiandong; Ma, Jie; Dong, Yingchun; Shen, Zhen; Ma, Henghui; Wang, Xuan; Shi, Shanshan; Wu, Jinrong; Lu, Guangming; Peng, Libo; Zhoud, Xiaojun
Abstract Eph receptors play important roles in the development of cancer. The present study aimed to investigate the expression of EphA1 and its clinicopathologic significance in esophageal squamous cell carcinoma (ESCC). The expression levels of the EphA1 transcript and protein were compared between ESCC and matched normal mucosa in the same patient. High expression levels of the EphA1 transcript and protein were detected in 25.6% (21/82) and 23.2% (19/82) of tumors compared with matched normal mucosa. The up‐regulation of EphA1 transcript in tumors was positively associated with differentiation (p = 0.002), disease stage (p = 0.034), and lymph node metastasis (p = 0.042). Increased expression of EphA1 protein in tumors was more often observed in patients with well‐differentiated tumors (p = 0.004), lymph node metastasis (p = 0.028), and advanced tumor stage (p = 0.008). EphA1 protein expression was detected in intraepithelial neoplasias as well. Decreased expression of EphA1 protein was detected in 65.2% (15/23) of samples with low‐grade neoplasia and in 85.3% (8/15) of samples with high‐grade intraepithelial neoplasia. Increased staining of EphA1 protein was not detected in low‐grade intraepithelial neoplasia samples, but was detected in 21.3% (2/15) of high‐grade intraepithelial neoplasia samples. Taken together, our results show that EphA1 appears to be a differentiation marker for esophageal squamous cells, and its increased expression is positively associated with lymph node metastasis and advanced disease stage.